IMPLEMENTASI PELAYANAN PERIZINAN BERUSAHA TERINTEGRASI SECARA ELEKTRONIK PADA PEMERINTAH KOTA YOGYAKARTA - Muhammad Roman Riandhi (Kajian Hukum, 2022)
The implementation of Online Single Submission (OSS) is an innovative idea in an effort to improve the business licensing service system in Indonesia by utilizing developments in information systems and technology which are directly supervised by the Investment Coordinating Board (BKPM) and OSS. Institutions as implementers at the central level. The Yogyakarta City Investment and One-Stop Integrated Services Service (DPMPTSP) as one of the implementers at the regional level is also required to make the implementation of OSS a success. Because the city of Yogyakarta has large investment potential. The aim of this research is to describe how OSS is implemented in the City of Yogyakarta as an innovation in public services. The approach method used in this research is the statutory approach, carried out by reviewing all statutory regulations relating to the legal issues being handled. Data analysis uses qualitative descriptive methods. The research results show that the implementation of OSS in Yogyakarta City has been widely socialized to the public because OSS is an innovation that is relatively profitable and easy to observe and has not undergone many changes compared to the previous system. However, as an integrated system, OSS still confuses business people. Apart from that, there have been several regulatory changes which have made it quite difficult to provide services. Even though it is easy to implement, in reality there are still several systems and regulations that still burden businesses and workers.